Initial single-center experience with the fully repositionable transfemoral lotus aortic valve system - Jarr, Kai-Uwe; Leuschner, Florian; Meder, Benjamin; Katus, Hugo; Bekeredjian, Raffi; Chorianopoulos, Emmanuel (The journal of invasive cardiology, 2017)
BACKGROUND: Transcatheter aortic valve replacement (TAVR) has become the standard therapy for patients with severe symptomatic aortic stenosis and unacceptable high risk for surgical aortic valve replacement. Several different devices for TAVR have been introduced so far, each of them with unique features. AIMS: To analyze our first real-world experience with the second- generation, mechanically expanded, fully repositionable transfemoral Lotus TAVR device (Boston Scientific). RESULTS: Between August 2014 and January 2016, a total of 298 patients were scheduled for transfemoral TAVR at our institution. Among them, 145 patients received a CoreValve/CoreValve Evolut R device (Medtronic), 90 patients received a Sapien 3 device (Edwards Lifesciences), and 63 patients were scheduled for Lotus TAVR device implantation based on access vessel size and annulus diameter. Of the 63 subsequent patients scheduled, 62 were successfully implanted. Short-term Valve Academic Research Consortium (VARC)-2 results at 30 days showed a 6.4% all-cause mortality, a 3.2% major stroke rate, a 36.5% new permanent pacemaker rate and 1.6% major vascular complications. Of note was the near absence of significant residual aortic regurgitation in the presence of a favorable hemodynamic profile even in patients with difficult anatomy. CONCLUSION: Our first real-time experience with the fully repositionable Lotus TAVR system mimics the results of early clinical studies like REPRISE II. Further next-generation modifications in combination with gaining experience with this new device will likely reduce the need for new permanent pacemaker implantation and vascular complications in the future.
Published online ahead of print on 2016 Nov 15
Keine DOI vorhanden
Gesehen am 16.08.2018